Preaching in Student Development at Tahfidzul Qur’an Al-Imam Ashim Islamic Boarding School in Makassar - Fahmi, Nurul; Tajibu, Kamaluddin; Muhammad, Firdaus (Jurnal Mercusuar, 2021)
The Tahfidzul Qur’an Al-Imam Ashim Makassar Islamic boarding school is striving to integrate secular knowledge with Islamic studies, with the vision of producing students who are Islamic, have memorized the Qur’an, understand its meaning, and practice its teachings. This is important to researchers because the issue of a separation between secular and religious knowledge is currently threatening in the era of technological development. The research results indicate that: 1) There are five processes implemented in student development, including student orientation, tahfiz coaching, ta’lim coaching, student life coaching, and briefings. 2) The mentoring methods applied by the boarding school include three methods, namely oral, practical, and written methods.